Hubungan Disiplin Kerja Dan Beban Kerja Dengan Kinerja Petugas Rekam Medis Di RSUD Ratu Zalecha Martapura - Thina Maria Kaleluny; Ni Wayan Kurnia Widya Wati; Isti Qomah; Nina Rahmadiliyani (Jurnal Kesehatan Indonesia, 2026)
Unit plays a crucial role in supporting the quality of healthcare services. The performance of medical record staff is influenced by work discipline and workload. High discipline enhances efficiency and adherence to procedures, whereas excessive workload can reduce work quality. A preliminary study at Ratu Zalecha Regional Hospital, Martapura, revealed low punctuality and compliance with standard operating procedures (SOPs). Among 43 staff members, only 13.95% arrived on time, and 65.11% had not completed their attendance records properly. This study aims to analyze the relationship between work discipline and workload with the performance of medical record staff at Ratu Zalecha Regional Hospital, Martapura. A quantitative method with a cross-sectional approach was used. The results showed that most staff had good work discipline (58.1%), light workload (58.1%), and good performance (60.5%). The Spearman Rho test showed a significant relationship between work discipline and performance (p = 0.013), and between workload and performance (p = 0.001). In conclusion, work discipline and workload significantly influence the performance of medical record staff.